LncRNA GAS5 Suppresses Colorectal Cancer Progress by Target miR-21/LIFR Axis. (24th August 2022) - Xie, Juan; Wang, Jing-Jing; Li, Ya-Jun; Wu, Jia; Gu, Xiao-Jing; Yang, Xiao-Rong
Abstract : GAS5 is abnormally high in colorectal cancer tissues, which is a specific expression of lncRNA in colorectal cancer (CRC). Nevertheless, its biological function in CRC has not been elucidated. The abnormal high expression of GAS5 in CRC is the specific expression of lncRNA in CRC. The purpose of our study is to explore the effect of GAS5 on CRC and its mechanism. The expression of GAS5 in 53 paired normal and colorectal cancer tissues and colorectal cancer cell lines was detected by real-time PCR. The biological effects of GAS5, miR-21, and LIFR were measured by functional assays, including wound healing, transwell assays, and in vivo assays. We ensured the carcinogenesis role of GAS5 in CRC in the xenograft nude model. The dual-luciferase reporter assay system and chromatin immunoprecipitation method were used for target evaluation and Western blot for verification. GAS5 was significantly decreased in tumor tissues and CRC cells, and the low expression of CAS5 in CRC promoted tumor metastasis and decreased the survival of patients. GAS5 knockdown increases the cell viability, inhibits apoptosis, and promotes migration. Xenografted tumors in nude mice studies showed that GAS5 knockdown promoted tumor growth and caused worse lesions in colorectal. Furthermore, GAS5 increases the expression level of target gene LIFR to promote the apoptosis of CRC cells by binding to miR-21. Our study revealed that a novel pathway about lncRNA GAS5 inhibited the proliferation and metastasis of CRC cells by targeting miR-21/LIFR which provides a new strategy to treat CRC.